Education in the genomics era: Generating high-quality genome assemblies in university courses. Issue 6 (3rd June 2020) - Prost, Stefan; Winter, Sven; De Raad, Jordi; Coimbra, Raphael T F; Wolf, Magnus; Nilsson, Maria A; Petersen, Malte; Gupta, Deepak K; Schell, Tilman; Lammers, Fritjof; Janke, Axel
Abstract: Recent advances in genome sequencing technologies have simplified the generation of genome data and reduced the costs for genome assemblies, even for complex genomes like those of vertebrates. More practically oriented genomic courses can prepare university students for the increasing importance of genomic data used in biological and medical research. Low-cost third-generation sequencing technology, along with publicly available data, can be used to teach students how to process genomic data, assemble full chromosome-level genomes, and publish the results in peer-reviewed journals, or preprint servers. Here we outline experiences gained from 2 master's-level courses and discuss practical considerations for teaching hands-on genome assembly courses.